Pengaruh Ukuran Legislatif, Kemakmuran Pemerintah Daerah, Ukuran Pemerintah Daerah dan Intergovernmental Revenue terhadap Kinerja Keuangan Pemerintah Daerah (Studi Pada Kabupaten/Kota Di Aceh Tahun 2010 s.d 2014) - Marhawai Marhawai (Jurnal Telaah dan Riset Akuntansi, 2015)
This study aimed to examine the effect of the legislative measure, the prosperity of the local government, the size of the local authority and intergovernmental revenue on the financial performance of local governments. This study is hypothesis testing with secondary data sources and being analyzed using path analysis. The population in this study are all districts / cities in Aceh government, amounting to 23 districts / cities with a span of years 2010 until 2014. The results showed that (1) the size of the legislature, the prosperity of the local government, the size of local government and intergovernmental revenue collectively the same effect on the financial performance of local government, (2) partially, the size of the legislature and the size of local government negatively affect the financial performance of local governments, (3) partially prosperity of local governments and intergovernmental revenue positive effect on the financial performance of local governments.KEYWORDS : The size of the legislature, the prosperity of the local government, the size of local government, intergovernmental revenue and financial performance of local governments